2017
DOI: 10.7150/jca.19819
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Benign and Malignant Diagnosis of Mediastinal and Hilar Lymph Nodes by Endobronchial Ultrasound Elastography

Abstract: Background and Objectives: Endobronchial ultrasound elastography is a new technique for describing the stiffness of tissue during endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA). The aims of this study were to investigate the diagnostic value of Endobronchial ultrasound (EBUS) elastography for distinguishing the difference between benign and malignant lymph nodes among mediastinal and hilar lymph nodes.Materials and Methods: From June 2015 to August 2015, 47 patients confirmed of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
57
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 13 publications
2
57
0
1
Order By: Relevance
“…Three studies used a scoring system like the color VAS scoring system, with comparable results [14, 18, 22]. He et al [14] reported best accuracy if the visualized color was over 50% blue, then indicative of malignancy with an accuracy of 73.7%.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Three studies used a scoring system like the color VAS scoring system, with comparable results [14, 18, 22]. He et al [14] reported best accuracy if the visualized color was over 50% blue, then indicative of malignancy with an accuracy of 73.7%.…”
Section: Discussionmentioning
confidence: 93%
“…He et al [14] reported best accuracy if the visualized color was over 50% blue, then indicative of malignancy with an accuracy of 73.7%. Huang et al [22] and Izumo et al [18] introduced an additional cut-off; only predominantly blue lesions were indicative of malignancy, while predominantly non-blue lesions were indicative of benign lymph nodes. By leaving out an intermediary group (part blue, part non-blue) they were able to report an overall accuracy in these categories of 91.4 and 96.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In any case cell blocks are essential when we are using biopsy techniques with needles (16). Elastography can also nowadays assist in the evaluation of a lesion/lymphadenopathy and with or without a previously positron emission tomography performed we can have the valuable information were to inject our needle and whether the investigated lesion/lymphadenopathy is benign or malignant or unspecified (19). Choosing needles were possible can definitely provide us tumor heterogenicity since ultrasound techniques provide us with visualisation of the needle while puncturing and therefore we can repeat the sample movement as many times as possible and from different parts of a lesion.…”
mentioning
confidence: 99%